PELATIHAN MATERI LOGIKA MATEMATIKA DAN INFORMATIKA BAGI PESERTA OSN SISWA SMA NEGERI 11 PURWOREJO - Latifah, Ummu Wachidatul; Ariyanto, Catur; Bahri, Saiful; Dewantara, Rizki; Siswanto, Irwan (Intimas, 2024)
Abstract The National Science Olympiad (OSN) is one of the competing events in the field of science at the elementary, junior and senior high school levels. The implementation of OSN does not only rely on students, but involves school contributions. SMA Negeri 11 Purworejo participates in several OSN fields, one of which is Informatics. OSN in Informatics includes Mathematical Logic material and the preparation of coding scripts based on Programming Algorithms. Training and debriefing of OSN materials is less than optimal due to the busyness of teachers. Based on these problems, a team of lecturers from the Bhakti Putra Bangsa Indonesia Institute of Business Technology and Health conducted coaching and debriefing for students participating in the Informatics OSN at SMA Negeri 11 Purworejo. Debriefing and deepening the material carried out by lecturers is one of the Community Service (PkM). The purpose of this service is to improve the competence of students participating in OSN Informatics so that they can better understand the material and strategies for solving OSN questions. The method in implementing OSN Informatics coaching consists of three stages, namely the first stage of needs analysis, the second stage of implementation and the third stage of evaluation. Based on observations during the coaching process, the results showed an increase in students' abilities. This can be seen from the students' ability to analyze and solve problems. The results can be seen from one of the students who passed the OSN Informatics at the Regency level and continued to the Provincial level. However, at this evaluation stage, some shortcomings were found so there needs to be an action plan for the next year's OSN preparation.Abstrak Olimpiade Sains Nasional (OSN) merupakan salah satu ajang berkompetensi di bidang sains tingkat SD, SMP dan SMA. Pelaksanaan OSN tidak hanya bertumpu pada siswa, namun melibatkan konstirbusi sekolah. SMA Negeri 11 Purworejo mengikuti beberapa bidang OSN, salah satunya Informatika. OSN bidang Informatika meliputi materi Logika Matematika dan penyusunan script koding yang berdasarkan oleh Algoritma Pemrograman. Pelatihan dan pembekalan materi OSN kurang maksimal karena kesibukan guru. Berdasarkan permasalahan tersebut, maka dilakukan pembinaan dan pembekalan materi pada siswa peserta OSN Informatika di SMA Negeri 11 Purworejo oleh tim dosen Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia. Pembekalan dan pendalaman materi yang dilakukan oleh dosen merupakan salah satu Pengabdian Kepada Masyarakat (PkM). Tujuan pengabdian ini untuk meningkatkan kompetensi siswa peserta OSN Informatika sehingga dapat lebih memahami materi dan strategi penyelesaian soal OSN. Metode dalam pelaksanaan pembinaan OSN Informatika terdiri dari tiga tahapan, yaitu tahap pertama analisis kebutuhan, tahap kedua pelaksanaan dan tahap ketiga evaluasi. Berdasarkan hasil pengamatan selama proses pembinaan, diperoleh hasil adanya peningkatan kemampuan siswa. Hal tersebut dapat terlihat dari kemampuan siswa dalam menganalisis dan menyelesaikan masalah. Hasil tersebut dapat terlihat ada salah satu siswa yang lolos OSN Informatika tingkat Kabupaten dan melanjutkan ke tingkat Provinsi. Namun, pada tahap evaluasi ini ditemukan beberapa kekurangan sehingga perlu ada rencana tindak lanjut untuk persiapan OSN tahun berikutnya.